THE IOTN INDEX - INDEX OF ORTHODONTIC TREATMENT NECESSITY - Roxana COJOCARU; Laura BEJAN; Larisa BOGDAN; Luisa COSTAN; Bogdan DRAGOMIR; Irina ZETU (Romanian Dental Association for Education, 2014)
Occlusal indices are defined as "instruments in epidemiological studies to determine the need for orthodontic treatment or the sum of deviations from normal occlusion, which can be used to evaluate patients individually and to assess a population group" where "occlusal anomalies are considered to be deviations from normal occlusion. The aim of occlusal indices is to determine in an objective way when malocclusion severity grade requires orthodontic treatment, to identify patients most entitled to benefit of orthodontic treatment (not only in terms of the type and severity of malocclusion but also in terms view of patient motivation and cooperation) and to prioritize patients according to need orthodontic treatment when resources are limited. Aesthetic component (AC) of the Index of orthodontic treatment Need led to the division of 10 degrees in three orthodontic treatment: grades 1-4 do not require orthodontic treatment; grades 5-7 are limited orthodontic treatment need; grades 8-10 is great need of treatment.